2008
DOI: 10.1152/physiolgenomics.00024.2008
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional adaptation to Clcn5 knockout in proximal tubules of mouse kidney

Abstract: Dent disease has multiple defects attributed to proximal tubule malfunction including low-molecular-weight proteinuria, aminoaciduria, phosphaturia, and glycosuria. To understand the changes in kidney function of the Clc5 chloride/proton exchanger gene knockout mouse model of Dent disease, we examined gene expression profiles from proximal S1 and S2 tubules of mouse kidneys. We found many changes in gene expression not known previously to be altered in this disease. Genes involved in lipid metabolism, organ de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…Then, with the aid of a stereoscopic microscope and fine forceps, the proximal tubules were dissected by hand for posterior RNA extraction (Wright et al., 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Then, with the aid of a stereoscopic microscope and fine forceps, the proximal tubules were dissected by hand for posterior RNA extraction (Wright et al., 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Midkine, which is highly expressed in proximal tubule cells, was downregulated, whereas the mRNA encoding lipocalin 2, which is expressed in the distal nephron, was upregulated [103]. Together with the unchanged serum levels of retinol and the increased amount of retinol binding protein in the urine of KO mice [68], one can suggest a mechanism similar to that described for 1,25(OH) 2 -vitamin D 3 .…”
Section: Hyperphosphaturia Hypercalciuria and Kidney Stones As Indimentioning
confidence: 68%
“…Both enzymes, the vitamin D 3 activating and degrading one, are regulated by PTH, with the transcription of the 25 (OH)-vitamin D 3 -1α-hydroxylase being augmented and the messenger RNA (mRNA) stability of the vitamin D 3 24-hydroxylase being decreased [100][101][102]. Indeed, as predicted by increased urinary PTH concentrations in the ClC-5 KO, 25(OH)-vitamin D 3 -1α-hydroxylase mRNA and protein levels are drastically elevated in KO mice, whereas vitamin D 3 24-hydroxylase mRNA is markedly decreased [18,49,103]. Another, potentially even more important Fig.…”
Section: Hyperphosphaturia Hypercalciuria and Kidney Stones As Indimentioning
confidence: 99%
“…However, the observed discrepancy could be explained by the use of different methodologies of gene ablation, KO versus KD (53). During development, gene ablation can be compensated for by genetic mechanisms that are in many cases poorly understood (21,54,55). Previous studies in mice with Gal3 KO showed involvement of Gal3 in regulating cell differentiation and morphogenesis, which could contribute, among other things, to changes in mast cell physiology (49,56).…”
Section: Discussionmentioning
confidence: 99%